Christian anti-Judaism and early object relations theory. (December 2018) - Hewitt, Marsha Aileen
The central ideas of early object relations theory are heavily inflected with Christian anti-Judaism, particularly as found in the work of Ian Dishart Suttie, now credited as the founder of this tradition. The critique of Freud launched by Suttie repudiates Freudian theory as a "disease" inextricably connected to Freud being a Jew. Suttie's portrayal of Judaism both conforms to and replicates those theological commitments that privilege a triumphalist, supersessionist Christianity that breaks with Judaism, understood as devoid of love, ethics, and social justice interests. The paper argues that the elements organizing the central concepts that structure Suttie's Christian prejudice constitute distorting ideological interests that circulate and shape important strands of contemporary object relations theory. Central to the authors discussed is a repudiation of Freud's theory of unconscious drives on the basis of privileging love and intersubjectivity as the motivators of human psychological development made possible by Jesus and Christianity. The paper demonstrates that contemporary object relations theory remains heavily indebted to Suttie while remaining oblivious to his explicit anti-Judaism.